Masker Tradisional Berbahan Daun Mimba (Azadirachta Indica A. Juss) dan Lemon untuk Mengatasi Masalah Kulit - Fatmasari, Fitria Hansyah (Journal of Beauty and Cosmetology (JBC), 2020)
Mimba or Azadirachta indica A. Juss. is a leaf type of shrub that is often used in religious purposes. This study was undertaken to describe the process of making mimba and lemon mask and determine the results of the application of the mask on acne prone skin. This study used qualitative descriptive research design. Data were collected using observation of the results of the mask application for ten women aged 20-30 years old. The study was conducted at Mandasari Surabaya beauty clinic. The results showed the making process of the traditional mask including the stages of washing, drying, making a powder, and mixing with lemon juice followed by application on acne face. After four weeks with twice treatments a week, the results showed that respondent's skin became smoother, moister, tighter, brighter, suppler, and cleaner with less acnes.